BENTUK PENYAJIAN PERTUNJUKKAN WAYANG ORANG DI KECAMATAN BATANG KUIS KABUPATEN DELI SERDANG - NITA ZURAIDAH (Gesture: Jurnal Seni Tari, 2014)
This research intent to know about form the presentation  demonstrating  people puppets in subdistrict of quiz barregency of deli serdangIn this. Research time conduded by during two months, that is July 2014 until September 2014. Research place reside in countryside of quiz bar.. Sampel at the research is two people technique of data collecting is observation, interview, study of bibliography and demonstration and analysis with descriptive method qualitative. To eliminate worn-out and they long its native land, they make the culture that is artistry wayang orang. Form its presentation is theme, manner move the, music accompaniment, arrange the cloth and arrange the beauty. Its theme is bandung bondowoso. Its motion manner  is own 4 scene but dance in demonstrating this in scene 1 and scene 2. First scene is concubine and dance the horse lumping. Scene to 2 dance depicting battlefield. Line the opening music is bandung bondowoso. Scene of its 1 music accompaniment is satria, to 2 is loro jonggrang, to 3 satria, to 4 is jingle genie. Cloth weared by that is boro-boro, irak irahan. Arrange the beauty is character of like prabu damarmoyo Keywords:peoplepuppe